Optimizing Transmission Line Matching Circuits - Novak, S. (Radioengineering Society, 1996)
When designing transmission line matching circuits, there exist often overlooked, additional, not much used, degree of choice in the selection of the transmission line impedance. In this work are presented results of CAD analysis for the two element transmission line matching networks, demonstrating that selecting matching circuits transmission lines with higher impedance, than usually used 50 or 75 ohms, can in most cases substantially decrease the physical dimension of the final matching circuit. Computer program, analyzing the influence of the matching line impedance on the length of the matching elements was developed and results are presented. It appears, that it is advantageous to choose matching circuits with high characteristic impedance. This results in a reduced dimension of the matching circuits.